On the need for pro-poor land administration in disaster risk management. Issue 357 (2nd November 2017) - Unger, E.-M.; Zevenbergen, J.; Bennett, R.
Abstract : There exists an intensifying and multifaceted relationship between rapid population growth, the increasing occurrence of natural disasters, and demands for land tenure security. Consequently, there is growing agreement on the need to adopt pro-poor land administration approaches, ones that better address the needs of the poor living in disaster prone contexts. Vulnerable communities and exposed lands could benefit from emerging pro-poor land administration, however, thus far, application of the pro-poor mind-set has gained minimal traction in the disaster risk management agenda. Using a research synthesis, existing evidence is analysed and consolidated, and a new inclusive conceptual framework is built; one that illustrates the underutilised potential for pro-poor land administration in disaster risk management. The developed framework explains the interactions between three identified and fundamental global change forces (people, land and disaster) and the three disaster risk drivers (vulnerability, exposure and hazard). The framework illustrates how pro-poor approaches can simultaneously have impacts on both land tenure security and disaster risk management. The conceptual framework is considered a first step toward an implementable strategy for applying pro-poor land administration technologies in the context of disaster risk management. Ultimately, pro-poor land administration should enable the poor to minimise vulnerabilities and disaster risks through an inclusive land tenure security approach to prevent, mitigate, prepare and respond to natural disasters.